The Impact and Benefits of the Independent Curriculum Learning Independent Campus during Online Learning in the COVID-19 Period - Chontina Siahaan; Sunengsih Simatupang; Familia Novita Simanjuntak; Laras Nadiananda Iswari; Sifra Rebeka Waruwu; Jitu Halomoan Lumbantoruan (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The research aims to determine the form of readiness in implementing the Merdeka Campus Curriculum. Many difficulties were experienced by students when learning online, namely 85.71% had difficulty understanding the concepts and 14% the principles used. This fact does not stand alone. The results of a survey of 120 students showed that 90% of the educators had difficulty implementing the material. There are 8 implementation programs at State Universities and Private Universities in Indonesia that are being implemented. This aims to involve students and lecturers in collaborating with schools and industry online and face to face. However, it is not yet known the impact on the positive. The method used in this study is descriptive qualitative with a constructivist paradigm. Data collection techniques by way of observation, interviews and distribution of instruments. The object is the university that organizes it and the subject is students and lecturers. The results of the study show that the implementation still varies because there are study programs that have implemented it and some that have not, because there are still obstacles, both internal and external. Universities need to provide adequate facilities, infrastructure and applications to implement the program. The Study Program also needs to prepare qualified lecturers in handling the courses offered. The conclusion in the research needs to be increased and active activities in each Study Program